Impact of Literacy on Working Population in Kushinagar District, Uttar Pradesh - Chaudhary, Dilip Kumar; Gownamani, D. (National Geographical Journal of India, 2022)
Literacy and workforce are the two main factors for the social and economic development of people, community, society, region and country. This study analyses the trend and pattern of literacy and workforce participation in Kushinagar district, U.P. over the last decade (2001 to 2011). The study also tries to find out the correlation between literacyand workforce participation for both the Census years of 2001 and 2011. The data has been collected from the secondary sources (mainly from District Census Handbook of Kushinagar, 2001 and 2011). Spearman’s Rank correlation has been used to find out the correlation between the literacy and workforce participation of the study area. The data has been analysed in MS excel software and the location map has been prepared on ArcGIS 10.1. Analysis of the data shows a negative correlation existing between literacy and workforce participation in the study area. The major finding reveals that, the trend in literacy is increasing whereas the workforce participation has been decreased during the last decade due to the population increase which leads to the declination of job opportunities.